[PP.19.10] THE ARCADIA-POL STUDY– INVOLVEMENT OF CERVICAL AND INTRACRANIAL ARTERIES IN RELATION TO VASCULAR COMPLICATIONS AND ASSOCIATED CLINICAL SYMPTOMS IN PATIENTS WITH RENAL FMD. (September 2017) - Swiatlowski, L.; Hanus, K.; Warchol-Celinska, E.; Januszewicz, M.; Michalowska, I.; Florczak, E.; Prejbisz, A.; Kadziela, J.; Widecka, K.; Soltysiak, M.; Rowinski, O.; Pajak, I.; et al.
Abstract : Objective: To assess the involvement of cervical and intracranial arteries and associated clinical symptoms in patients with renal fibromuscular dysplasia (FMD) enrolled into ARCADIA-POL study. Design and method: From 144 patients with confirmed FMD enrolled into ARCADIA-POL study in 2015, 127 patients (104F, 23 M, mean age:44.8 ± 15.9 years) were analyzed. All patients underwent clinical evaluation: ABPM, biochemical evaluation, biobanking, duplex Doppler of cervical and abdominal arteries and whole body angio-CT including cervical and intracranial arteries. Results: Among 127 patients with renal FMD, 31 (24.4%) had coexisting FMD lesions in cervical and/or intracranial arteries and/or intracranial aneurysms: 15 (11.8%) pts in carotid, 4 (3.1%) pts in vertebral and 19 (15.0%) pts in intracranial arteries. Dissections of carotid arteries were found in 4 (3.2%) pts and vertebral artery dissections in 3 (2.4%) pts. In 3 (2.4%) pts internal carotid artery aneurysm was found. 12 (9.5%) pts had intracranial aneurysms: 9 (7.1%) pts had one aneurysm, 2 (1.6%) pts 2 aneurysms, 1 (0.8%) pts 3 aneurysms and 1 (0.8%) pt 4 intracranial aneurysms. Patients with and without cervical and/or intracranial FMD lesions didn't differ in terms of age, gender, clinical and ambulatory blood pressure levels, hypertension prevalence and number of antihypertensive medications. There was also no difference in the incidence of cervical and/or intracranial FMD lesions in patients with multifocal and unifocal lesions in renal arteries. There were no significant differences in the prevalence of symptoms such as headaches, tinnitus, dizziness and cervical bruits between the patients. There was only a significant difference in the presence of Horner's syndrome between patients with and without cervical and/or intracranial FMD (12.9% vs.2.4%; p = 0.017, respectively). There was no difference in the prevalence of stroke, transient ischemic attack or intracranial bleeding between the groups. Conclusions: There were no specific clinical features suggesting the presence of FMD lesions and vascular complications in cervical and/or intracranial arteries in patients with confirmed renal FMD included into ARCADIA-POL STUDY. Our study showed that systematic evaluation of cervical and intracranial arteries in patients with renal FMD resulted in revealing relatively high prevalence of FMD lesions and vascular complications in cervical and/or intracranial arteries.